PENGETAHUAN DENGAN PERAN PERAWAT DALAM PENANGANAN TRAUMA MUSKULOSKELETAL DI RUANG UGD RSUD Dr MM DUNDA LIMBOTO - Pipin Yunus; Arifin Umar; Noval Ismail (Universitas Muhammadiyah Gorontalo, 2020)
Trauma is a condition where a person experience shock or loss because of an incidence. The most frequent causes of trauma are traffic accidents, workplace accidents, sports and household tasks. Musculoskeletal system trauma is often found in the era of high-speed vehicles as it is today. In addition, the incidence of muskuloskeletal trauma increases, largely due to an increase of routine physical exercise of people such as jogging, running and other sports activities. This research aimed to determine the relationship between knowledge and the role of nurse in handling musculoskeletal trauma in the emergency room of Dr. M.M Dunda hospital. The research design was a quantitative correlational with cross-sectional approach. The researcher analyzed the data by Chi-Square test with significance level <0.05. The results indicated that there is a relationship between knowledge and the role of nurses in the handling of musculoskeletal trauma with P value of 0.02 <α 0.05. It is suggested that nurses are able to improve their competence in handling musculoskeletal trauma.